CITRA SANTRI PESANTREN DALAM CUPLIKAN FILM THE SANTRI - Hidayat, Mansur (KOMUNIKE, 2020)
The appearance of the trailer for The Santri movie has sparked various responses on the internet, this can be observed from the existence of parties who are pro and contra with the movie trailer. This difference can be seen from the way the audience responds to and interpret the contents of the movie trailer. This study can understand the image of the student at Islamic Boarding School in the movie trailer of The Santri which can be seen through the account NU Channel on YouTube. The study used a descriptive qualitative approach model with content analysis on movie trailers. The results of the study show that the image of the student at an Islamic Boarding School in the movie trailer of The Santri can be divided into two parts, namely: first, an explicit image such as students must have self-confidence, have high dreams, love religion and their nation, have a good faith, and be a loyal friend. Second, implicit images such as students who have a simple, tough, and brave image, accept differences, and are open-minded.